THE RELATIONSHIP BETWEEN TRADING VOLUME AND PRICE VOLATILITY OF SHARES IN THE NAIROBI SECURITIES EXCHANGE - ODHIAMBO GWORO, COLLINCE (IJRDO - Journal of Business Management, 2016)
This study intended to examine the price- volume movements in the NSE, in order to determine the impact of changes in trade volume on the volatility of stock prices. Traded volume is the measure of how many trades take place for a security or on an exchange on a given trading day. A high trading volume is an indicator of a high levelof interest in a security at its current price. The research design was a correlational study and the population of study consisted of all the 20 companies forming the NSE20 – share index by December 31, 2011. The sample consisted of 14 companies continuously forming the NSE 20-share index between the periods January 2007 – 31 stDecember, 2011. Secondary data for the period was collected from NSE data bank. Purposive sampling was used. The sample of 14 was based on the fact that some companies such as Uchumi Ltd and CMC motors had been suspended while Athi River mining co, Safaricom and Equity bank were included in the index in 2008 and KenolKobil was removed from the index in 2009. Volume of shares was computed using the average monthly traded volumes while share price volatility was determined using the standard deviation. Karl pearson’s correlation coefficient model was used for the purpose of analysis to determine whether there exist a relationship between thevariables. A regression model was also used to further assert the outcome of the study. The T-tests were below 0.5 which was insignificant and the R2 also were below 0.5 indicating that major variations of price were explained by other variables other than changes in traded volumes. It was concluded that there is a weak correlation between traded volume and the share price volatility of listed firms at the NSE. It is however recommended that a study of similar nature to be carried out on all the listed companies to give a more varied and valid conclusion.